The evolution of educational wage differentials for women and men in Germany, from 1996 to 2019 - Jessica Ordemann; Friedhelm Pfeiffer (Journal for Labour Market Research, 2022)
This paper studies the evolution of three higher education wage differentials from 1996 to 2019 in Germany. We distinguish between degrees from academic universities, degrees from universities of applied sciences, and the master craftsmancertificate. The educational reference category is a standard degree within the German vocational education and training system. Based on samples of male and female workers from the Socio-Economic Panel Study (SOEP), regression methods show that all three educational wage differentials in 2019 exceeded the ones in 1996. However, workers graduating from universities experienced an inverse u-shape pattern with a maximum of about 0.5 log points around 2012. Since then, their wage differential decreased by nearly ten percent (about 0.045 log points). Although the decrease is not statistically significant at conventional levels, we think that nearly ten percent can be regarded as economically meaningful. We argue that this pattern is related to university expansion and changes in graduates' subject-choice composition during that expansion. The paper concludes with a discussion of possible alternative explanations.
Keywords: J31; J16; I23; I26; 330; Educational Wage Diferentials; Gender Gaps; Higher Education; Returns to Education